Identity formation in the lyrics of Malaysian Chinese pop songs - Wong, Siew Ki (2019)
Since independence, Chinese community in Malaysia has undergone identity modification through a series of processes, including immigration and assimilation to become a part of the country. Due to differences in racial, cultural and nationality recognitions, Chinese community is facing difficulty and confusion with their identity. How did Malaysian Chinese come to accept their nationality over the past decades? What were some cultural, racial and nationality obstacles faced to come to where they are today? This study aims to scrutinise social thinking of the Chinese community on their identity in the past decades in order to grasp a better understanding of Malaysian Chinese. Popular literature is the closest to one’s life, it is widely enjoyed by the masses. This is because popular literature is easy to understand and can be easily accessed. Song lyrics is one of the favourable aspects in popular literature. Today, songs have become one of the most important factors in shaping societies in the world. Thousands of new songs are produced every year, but studies on them are limited. It was not until recent years that related researches started to take place in China, Hong Kong, Taiwan and Singapore. However, in Malaysia, research in this field of study is still lacking. Song lyrics is one of the most important elements in literature. The content, structure or style of lyrics can effectively reflect the characteristics of a society. This thesis aims to identify the relationship between Chinese pop songs lyrics and identity formation among Malaysian Chinese by looking into the history between these two notions. The ultimate purpose is to demonstrate the important influence of popular literature in cultural identity shaping among Malaysian Chinese.